Advances in Illicit Drug Portable Analytical Devices at Points of Care - Ghadeer M. M. Abdelaal (Perspective of Recent Advances in Medical Research Vol. 12, 2023)
Introduction: Illicit drug consumption and its associated criminal activities have reached alarming proportions in recent years. To overcome this crisis, a new decentralization trend of laboratory confirmatory methods has received considerable attention from scientists to suit points of care (POC). The typical confirmatory standards for drug analysis are gas chromatography-mass spectrometry (GC-MS), and Liquid chromatography-tandem-mass spectrometry (LC-tandem-MS). Nonetheless, these techniques employ large laboratory equipment, extensive sample preparation, and long analytical time that are inappropriate for in-field drug testing. Aim: Discuss the recent advances in illicit drug portable analytical devices at POC. Results: The current progress in portable drug analytical devices is primarily attributed to the emergence of various miniaturized platforms. This review focuses on miniature ambient ionization MS, electrochemical sensors (screen printed electrodes, aptasensors, and nanosensors), paper-based systems (lab on paper/ Lab on a chip), handheld ion mobility spectrometer (IMS), portable Raman spectroscopy (surface-enhanced Raman scattering-SERS) and portable near-infrared (NIR) spectroscopy. Conclusion: Miniature ambient ionization MS is very rapid with no required sample preparation; however, it is more expensive than other alternatives. Electrochemical sensors are quick, inexpensive, and sensitive devices, but selectivity can be affected by shelf life and storage conditions. Despite lab on paper being easy, rapid, and requiring minimal amounts of reagents, it has lower sensitivity and selectivity when compared to other instrumental detectors. Consequently, the most appropriate portable devices for in situ accurate drug analysis are handheld IMS, which is highly sensitive, selective and rapidly identifies compounds including isomers, and portable Raman, and NIR spectroscopies for their reasonable costs, easy, and quick real-time analysis within seconds, in addition to their coupling with novel smartphone applications.